A new species of Entomobrya Rondani, 1861 (Collembola, Entomobryidae, Entomobryinae) from Brazil, including new records of E. barbata Siqueira & Bellini, 2020 - Viana, Stéphanie Dos Santos; de Morais, José Wellington; Cipola, Nikolas Gioia (Zootaxa, 2022)
Herein we describe a new species of Entomobrya Rondani from Cerrado biome, Brazil. Entomobrya uai sp. nov. differs from its congeners in having triangle-shaped spot on trunk, dorsal chaetotaxy pattern, unguis morphology, unguiculus inner lamella truncate, and manubrial plate with 9–13 chaetae and 3 pseudopores. Entomobrya barbata Siqueira & Bellini known only from its type locality (Caatinga domain, Bahia state, Brazil), is herein recorded from Atlantic Forest (Minas Gerais, Paraná and Santa Catarina states) and Cerrado (Goiás state) biomes for the first time. The record of E. spectabilis Reuter in Brazil is herein dismissed due to a probable misidentification with E. barbata. From the description of E. uai sp. nov. and new records of E. barbata, the number of Entomobrya species in Brazil increased from 11 to 12 endemic species, and the genus is now recorded from 14 Brazilian states. In addition, this is the first record of a Collembola species from Distrito Federal and Goiás state, Brazil.